The impact of work stress on human resource performance in healthcare institutions: A case study of the Public Neighborhood Health Institution of Sidi M'hamed Ben Ali Relizane - Salah, Aissaoui; Fethi, Benzaoucha; Tayyib, Besseklal; Abdelkader, Bouroumana (The International tax journal, 2026)
This study aimed to measure the impact of work pressures on human resource performance in health sector institutions. The study sample included (60) workers in the public institution of neighborhood health Sidi Mohamed Ben Ali Relizane. The questionnaire was used as a tool for collecting information and the SPSS program version 25 was used to analyze the data. The study hypotheses were tested using the arithmetic mean, standard deviation, and simple linear regression analysis. The study concluded that there is a low level of work pressures in its various dimensions, and a high level of human resource performance. The results also showed that there is no statistically significant impact of work pressures in its various dimensions on human resource performance. The study concluded by presenting some suggestions that we believe will serve decision makers.